Экспериментальная установка для измерений параметров сложных составных сетей содержащих спутниковый сегмент - Марчук, А. В. (ХНУРЭ, 2009)
The experimental facility is developed for parameters measurements of complex composite networks containing the satellite segment.
Keywords: спутниковый сегмент; сложные составные сети